Analisis Strategi Pengembangan Usaha Melalui Matriks Swot pada Coffee Shop For Good Luck - Darvianti Darvianti; M. Yusuf; Paisal Paisal (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to identify and analyze the business development strategy of Coffee Shop For Good Luck by focusing on four key aspects: production, human resources, marketing, and finance. A descriptive quantitative approach was employed using SWOT analysis. Data were collected from 35 respondents. The results reveal that Coffee Shop For Good Luck possesses 6 strengths, 7 weaknesses, 5 opportunities, and 6 threats. The most significant internal strength lies in the attractive concept and well-organized layout (weight score: 0.285), while the main weakness is its less strategic location (0.051). Externally, the most impactful opportunity is the potential for collaboration with influencers (0.352), and the primary threat is the emergence of new coffee shops in the surrounding area (0.052). Based on the SWOT diagram, the business is positioned in Quadrant I (score: 2.18; 2.25), indicating a favorable situation with strong internal capabilities and external opportunities. Therefore, the recommended strategy is an aggressive growth strategy to fully leverage the business's strengths and opportunities.